p53 is a key molecular target of ursodeoxycholic acid in regulating apoptosis - Amaral, Joana D. (2015)
p53 plays an important role in regulating expression of genes that mediate cell cycle progression and/or apoptosis. In addition, we have previously shown that the hydrophilic bile acid ursodeoxycholic acid (UDCA) prevents transforming growth factor beta 1-induced p53 stabilization and apoptosis in primary rat hepatocytes. Therefore, we hypothesized that p53 may represent an important target in bile acid-induced modulation of apoptosis and cell survival. In this study we demonstrated that UDCA reduces p53 transcriptional activity, thereby preventing its ability to induce Bax expression, mitochondrial translocation, cytochrome c release, and apoptosis in primary rat hepatocytes. More importantly, bile acid inhibition of p53-induced apoptosis was associated with decreased p53 DNA binding activity. Subcellular localization of p53 was also altered by UDCA. Both events appear to be related with increased association between p53 and its direct repressor, Mdm-2. In conclusion, these results further clarify the antiapoptotic mechanism of UDCA and suggest that modulation of Mdm-2/p53 interaction is a prime target for this bile acid.